Challenges of Adopting Artificial Intelligence (AI) In the Healthcare Sector: A Project Management Perspective - Temitope Wisdom Olaitan (WORLD JOURNAL OF INNOVATION AND MODERN TECHNOLOGY, 2026)
The aim of this study is to investigate the challenges of AI adoption and implementation in healthcare project management in Imo State, Nigeria. Quantitative research methodology was adopted for the study. Purposive and snowball sampling techniques were used to select 315 professionals from the population of 385. The sample size was determined using Krejcie and Morgan's method. Participant insight was assessed using a Likert-scale structured questionnaire. The data was analysed by descriptive statistics, presented through frequency distributions through IBM SPSS statistics version 26.0. The key objectives of the study were analysed using the Severity Index (SI). The findings showed that the most significant challenges bedevilling AI adoption in healthcare through the project management approach includes lack of skilled professionals and insufficient training (SI=0.3297), followed by issues related to data privacy and security (SI=0.327), biases in data (SI=0.326), limited health data (SI=0.302), cost and resource limitations (SI=0.300), and issues with transparency and accountability (SI=0.278). The findings will improve the existing understanding of AI incorporation in healthcare management and provide valuable guidance to healthcare executives and technology innovators seeking to foster AI-enabled innovations in healthcare project management.